How to forage for wild foods without dying : an absolute beginner's guide to identifying 40 edible wild plants - Zachos, Ellen (Storey Publishing, 2023)
"How to Forage for Wild Foods without Dying is a book for anyone who likes to go on nature walks and would like to learn about the edible plants they're most likely to come across--no matter what region they're in. Author Ellen Zachos shares her considerable expertise, acquired over decades of foraging in every part of North America. She offers clear, concise descriptions of edible wild plants, in addition to any potential lookalikes, as well as critical information about proper harvesting, processing, and cooking"--